Short-Term Inhalation of Ultrafine Zinc Particles Could Alleviate Cardiac Dysfunctions in Rats of Myocardial Infarction - Li, Li; Niu, Pei; Wang, Xuan; Bing, Fangbo; Tan, Wenchang; Huo, Yunlong (Frontiers in Bioengineering and Biotechnology, 2021)
It is not clear for inhalation of ultrafine metal particles in air pollution to impair human health. In the study, we aimed to investigate whether short-term (4 weeks) inhalation of ultrafine zinc particles could deteriorate the cardiac and hemodynamic functions in rats of myocardial infarction (MI). MI was induced in Wistar rats through coronary artery ligation surgery and given an inhalation of ultrafine zinc particles for 4 weeks (post-MI 4 weeks, 4 days per week and 4 hours per day). Cardiac strain and strain rate were quantified by the speckle tracking echocardiography. The pressure and flow wave were recorded in the carotid artery and analyzed by using the Womersley model. Myocardial infarction resulted in the LV wall thinning, LV cavity dilation, remarkable decrease of ejection fraction, dp/dt Max, –dp/dt Min, myocardial strain and strain rates, and increased LV end-diastolic pressure, as well as impaired hemodynamic environment. The short-term inhalation of ultrafine zinc particles significantly alleviated cardiac and hemodynamic dysfunctions, which could protect from the MI-induced myocardial and hemodynamic impairments albeit it is unknown for the long-term inhalation.